This fight is our fight [compact disc, unabridged] : the battle to save America's middle class - Warren, Elizabeth (Macmillan Audio, 2017)
The senator shares stories of her battles in the Senate fighting for the working class, describing the experiences of middle-class Americans struggling to survive.